ANALYSIS OF USER SATISFACTION ON SELF-LOAN SERVICES IN ISLAMIC STATE INSTITUTE (IAIN)PURWOKERTO LIBRARY - Antasari, Indah Wijaya; Chakim, Sulkhan (EARR (Educational Administration Research and Review), 2019)
This study aims to determine the level of user satisfaction on the self-loan services in the Library of IAIN Purwokerto. The methodology applies  a descriptive quantitative approach on the population of active visitors. The monthly mean visitors in 2018 is 9,810 people. The sampling technique uses Slovin formula with 10% sampling error of 100 respondents. Data is collected through methods of observation, questionnaire and documentation. Results indicate users satisfaction on each variables are scored at 3.03 on facilities, 3.12 on officers services, and 3.14 on the access, all out of 4 digit scores. The overall mean score 3.10 indicates a good user satisfactory level. The feedback from respondents includes needs on additional computers, library collections (books) placed on shelf a match  numerical classification, and an increase in the number of circulatory books.